Scorch - Damico, Gina (Houghton Mifflin Harcourt, 2012)
Sixteen-year-old grim reaper Lex Bartleby tries to redeem herself among her fellow Grims by finding renegade Zara, who is indiscriminately damning souls, and stopping her once and for all.